Soft Elastomers with Ionic Liquid‐Filled Cavities as Strain Isolating Substrates for Wearable Electronics. Issue 9 (27th December 2016) - Ma, Yinji; Pharr, Matt; Wang, Liang; Kim, Jeonghyun; Liu, Yuhao; Xue, Yeguang; Ning, Rui; Wang, Xiufeng; Chung, Ha Uk; Feng, Xue; Rogers, John A.; Huang, Yonggang
Abstract : Managing the mechanical mismatch between hard semiconductor components and soft biological tissues represents a key challenge in the development of advanced forms of wearable electronic devices. An ultralow modulus material or a liquid that surrounds the electronics and resides in a thin elastomeric shell provides a strain‐isolation effect that enhances not only the wearability but also the range of stretchability in suitably designed devices. The results presented here build on these concepts by (1) replacing traditional liquids explored in the past, which have some nonnegligible vapor pressure and finite permeability through the encapsulating elastomers, with ionic liquids to eliminate any possibility for leakage or evaporation, and (2) positioning the liquid between the electronics and the skin, within an enclosed, elastomeric microfluidic space, but not in direct contact with the active elements of the system, to avoid any negative consequences on electronic performance. Combined experimental and theoretical results establish the strain‐isolating effects of this system, and the considerations that dictate mechanical collapse of the fluid‐filled cavity. Examples in skin‐mounted wearable include wireless sensors for measuring temperature and wired systems for recording mechano‐acoustic responses. Abstract : An ionic liquid fills a microfluidic space, or cavity, defined in a low modulus elastomeric substrate, which isolates the underlying skin from the electronics above, without any direct contact with either. Electronic systems built on this platform enhance not only the wearability but also the range of stretchability in suitably designed devices.